Crystal facet-dependent activity of α-Mn2O3 for oxygen reduction and oxygen evolution reactions. (3rd September 2020) - Wang, Ying; Hu, Tianjun; Chen, Yan; Yuan, Hongjie; Qiao, Yanting
Abstract: Electrocatalysts with different morphologies and specific exposed facets usually exhibit distinguished activities. In this work, two α-Mn2 O3 with different morphologies and crystal facets were successfully prepared by solvothermal method and investigated as ORR/OER bifunctional catalysts for the first time. The results showed that the catalytic performance is affected by the crystal facet of α-Mn2 O3, and the α-Mn2 O3 -cubic has better bifunctional activity than α-Mn2 O3 -octahedra. As revealed by catalyst characterization, the enhanced activity is originated with the nature of the exposed α-Mn2 O3 (100) facet. The (100) facet with abundant low-coordinated surface oxygen sites makes the formation of more oxygen vacancies, which can improve the charge transfer and optimize the adsorption energies for intermediates, thereby enhancing the bifunctional activity for ORR/OER. This work highlights the correlation between OER/ORR activities and exposed crystal planes of α-Mn2 O3 catalysts and it may deepen the understanding of facetdependent activity of α-Mn2 O3 and points out a strategy to improve their catalytic activity by crystal facet engineering. Highlights: Two α-Mn2 O3 with different morphologies were prepared by solvothermal method. The ORR/OER activity depended on the crystal shapes and exposed crystal facets. α-Mn2 O3 –C with predominant (001) facet exhibits better electrocatalytic activity.